2020
DOI: 10.1016/j.forsciint.2019.110060
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for the assessment of inflicted head injury by shaking trauma in infants: a systematic review

Abstract: In order to investigate potential causal relations between the shaking of infants and injuries, biomechanical studies compare brain and skull dynamic behavior during shaking to injury thresholds. However, performing shaking tolerance research on infants, either in vivo or ex vivo, is extremely difficult, if not impossible. Therefore, infant injury thresholds are usually estimated by scaling or extrapolating adult or animal data obtained from crash tests or whiplash experiments. However, it is doubtful whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Recent reviews have concluded that thresholds, based on experiments or models, used to assess shaking trauma are of low quality and questionable use 56,57 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews have concluded that thresholds, based on experiments or models, used to assess shaking trauma are of low quality and questionable use 56,57 …”
Section: Resultsmentioning
confidence: 99%
“…Recent reviews have concluded that thresholds, based on experiments or models, used to assess shaking trauma are of low quality and questionable use. 56,57 Zhu et al 58 conducted a combined autopsy and modelling study of 137 bridging veins from six adults. Based on bridging vein diameters and angles relative to the SSS, they calculated that venous thrombosis would occur more easily in wider bridging veins >1.2 mm, and when angles at the entry points were small (<65°).…”
Section: Biomechanicsmentioning
confidence: 99%
“…Commonly used shaking injury thresholds have recently been called into question for various reasons. 19 Many such thresholds have not been properly validated for applicability to infants, and few take into account the very different loading patterns found in shaking versus impacts. Although impacts may cause large impulse transfers by short duration, high-intensity peaks, shaking may transfer just as large or even larger impulses with lower maximum forces, but over longer and repeated cycles.…”
Section: Discussionmentioning
confidence: 99%
“…2 Approximately 25% of SBS injuries are fatal, 1 and survivors may experience developmental delays, behavioral disorders, seizures, and loss of vision. 3−5 There is little consensus among physicians and researchers that shaking alone causes the injuries associated with SBS, 6 and the American Academy of Pediatrics (AAP) and the Center for Disease Control and Prevention (CDC) recommend pediatricians use the term AHT instead of SBS to avoid specifying a mechanism of injury. 7,8 Despite recommendations from AAP and CDC, medical professionals continue to diagnose SBS, suggesting that both AHT and SBS are relevant diagnoses and definitions of abuse.…”
Section: Introductionmentioning
confidence: 99%